The role of adjuvant chemotherapy in the management of acute promyelocytic leukemia differentiation syndrome - LaBella, Dominic; Regan, Samuel; Konig, Heiko; Egan, Daniel N.; Bailey, Neil A.; Mawad, Raya; Gilbert, Morgan; Pagel, John M.; Pu, Jeffrey J. (Frontiers in Oncology, 2022)
Acute Promyelocytic Leukemia (APL) is characterized by the t(15;17) chromosomal translocation resulting in a PML-RARA fusion protein. The all-trans-retinoic acid (ATRA) and Arsenic Trioxide (ATO) only regimens have demonstrated success in treating low- and intermediate-risk patients. However, induction with ATRA/ATO only regimens have been showing increased incidence of differentiation syndrome (DS), a potentially lethal complication, traditionally treated with dexamethasone. We conducted a three-institution retrospective study, aiming to evaluate the role of short-term adjuvant chemotherapy in managing moderate DS for patients with low- or intermediate-risk APL initially treated with ATRA/ATO only protocols. We evaluated the difference in incidence and duration of moderate DS in APL patients who were treated with ATRA/ATO with or without adjuvant chemotherapy. Fifty-seven low- or intermediate-risk APL patients were retrospectively identified and included for this study; 36 patients received ATRA/ATO only induction treatment, and 21 patients received ATRA/ATO/adjuvant chemotherapy combination induction therapy. Similar proportions of patients experienced DS in both groups (66.7% vs. 81.0%, P = 0.246). The median duration of DS resolution in patients receiving ATRA/ATO only was 17 days (n = 23), and in patients receiving combination therapy was 8 days (n = 16) (P = 0.0001). The lengths of hospital stay in patients receiving ATRO/ATO only was 38 days (n = 7), and in patients receiving combination therapy was 14 days (n = 17) (P = 0.0007). In conclusion, adding adjuvant chemotherapy to ATRA/ATO only protocol may reduce the duration of DS and the length of hospital stay during APL induction treatment.